Nutritional status assessment of under five years’ children of Magar Community of Nisdi Rural Municipality, Palpa - Raikhola, Pushkar Singh; Gaire, Tara; Pathak, Krishna Prasad (International Research Journal of MMC, 2021)
Malnutrition is one of the most important public health problems of developing countries where resources are very limited. The common cause of malnutrition is lack of access to the nutritious food, poor breastfeeding practices, offering the wrong foods, and not ensuring that the child gets enough nutritious food. The prevailing high rate of child under-nutrition in the country is one of the major contributing factors of under-five mortality. We aimed to find out nutritional status of children under five years in Magar community group who are financially poor. This was applied cross-sectional study in 115 children (under 5 years) of Magar ethnic group of Nisdi Rural Municipality, Palpa to assess situation of the nutrition . Statistical analysis was performed using SPSS 20.0 version for the anlysis the results. This study revealed that 96.5% children were fed with colostrum and 60.2% of the children out of 108 children aged 6-59 months were exclusively breastfed for 6 months. Likewise, 56.5% children received timely initiation of complementary feeding. Out of 115 children, 60% were still continuing breastfeeding whereas 1.7% dropped in less than 2 year and 38.3% continued for more than 2 years. Based on Gomez-classification for weight for age (Underweight), among 115 children only 26.1% children aged under 59 months were normal. While, more than half (53.9%) were mildly malnourished, 16.5% were moderately malnourished and 3.5% were severely malnourished. Based on Waterlow‘s classification for Weight for height (wasting), less than half (46.1%) children aged under 59 months were normal. While, 40.9% were mildly malnourished, 10.4% were moderately malnourished and 2.6% were severely malnourished. Similarly, based on Waterlow‘s classification for Height for age (Stunting), 52.2% children aged under 59 months were normal. While, 23.5% were mildly malnourished, 14.8% were moderately malnourished and 9.6% were severely malnourished. This study concluded that most of the children under 5 years’ age of Nisdi Rural Municipality, Palpa were malnourished.